Strategy of Padang City Baznas In Collecting Non ASN Zakat Funds - Ibnu Amin; Faisal Efendi; Mardianton Mardianton (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: This study analyzes how the Padang City Baznas strategy in collecting zakat funds from Non-ASN, Padang City Baznas is able to collect so many zakat funds, so this can be a reference for Baznas in Indonesia.Design/Method/Approach: The author uses data collection techniques in the form of observations and interviews. The data analysis technique used in this study is descriptive and qualitative, which aims to describe the real events that occur in the field.Findings: The Head of Collection Division has a contract employee, where the contract employee is not the same as an ordinary employee, the contract employee receives an honorarium in one month amounting to Rp. 2,100,000 (two million one hundred million rupiah) and must be able to collect zakat as much as Rp. 20,000,000.00 (twenty million rupiah) per month and meaning that within one year the contract employee must be able to collect zakat funds of Rp. 240,000,000.00, (two hundred and forty million rupiah) per year, but if the contract employee is able to exceed the specified limit then the contract employee gets or is given 5% of as many as these excess. In addition, the strategy carried out by Baznas Padang City is to spread in the form of boxes and piggy bank in various places such as restaurants and shops.Originality/Values: The contribution of this research can provide valuable information related to education financing and become a reference of choice for other schools in the expenditure costs that have been set by the government and do not ignore the provisions in sharia economy.